A Reverse Mortgage as an Opportunity to Cover the Costs of Long‑term Care – Solutions in the European Countries - Warchlewska, Anna; Iwański, Rafał (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The progressive aging of the population forces the world to face new challenges, especially in the financial sector. The paper strives to present possible forms of coverage of long‑term care in the private and public market. A reverse mortgage and perpetuity are a point of consideration for the world of science and practice but they are also associated with a great deal of controversy. According to the authors of this paper, the theme requires cognitive exploration. The aim of the study is to diagnose the current situation of financial markets in selected European countries related to a reverse mortgage and perpetuity. Assuming that the sources of funding the current needs of elderly people available on the financial market are voluntary ones, it is necessary to present a forecast covering the costs of long‑term care from public funds.